Hubungan Pengetahuan Lingkungan Hidup dengan Perilaku Pemilihan Plastik Biodegradable pada Mahasiswa Biologi Universitas Negeri Jakarta - Karina Pravitasari; Diana Vivanti Sigit; Ernawati Ernawati (NUCLEUS, 2022)
The use of plastics which tend to increase in turn can have a negative impact on the environment. Students as young people are required to overcome these problems. One solution is to implement the electoral behavior of biodegradable plastic. To election of biodegradable plastic, students needed environmental knowledge. This study aimed to determine the association between environmental knowledge with electoral behavior of biodegradable plastic  students of Biology UNJ. This research was conducted at the Biology Education Studies Program and Biological Studies Program UNJ in November-December 2016. The research used descriptive method through correlational study. Sampling by technique sampling was done through simple random sampling technique with 79 students of Biology branch of 2014. Data showed in normal distribution and homogeneous. The regression model obtained was Y= 88,124 + 0,223X. The correlation coefficient obtained was 0.223, which means there is a positive corelation between environmental knowledge and electoral behavior of biodegradable plastic  in students of Biology UNJ. This research can provide guidance the students to use biodegradable plastics and protect the environment from the ravages of conventional plastics.